Driving Permit Service Strategy (SIM) in Siak Regency - Rosna Meilani; Rd. Siti Sofro Sidiq; Swis Tantoro; Seger Sugiyanto (SEAN Institute, 2023)
A driver's license is a special requirement that must be owned by the public to drive a motor vehicle. However, there are still 1,075 people who do not have a SIM in 2022. The purpose of this study is to analyze the strategies and obstacles of SIM services in Siak District. The research method used is descriptive qualitative with subject determination using purposive sampling consisting of SIM service officers and SIM issuance applicants. The results of the study found that there are several strategies used to optimize SIM services, namely 1) The strategy of identifying the main determinants of SIM services. 2) The strategy of managing the expectations of applicants who receive services from SIM services. 3) Strategy of managing evidence of quality in SIM services. 4) The strategy of educating the public is carried out by SIM services where service officers help the public or applicants to get education related to SIM either from socialization, e-books, or tutoring. 5) The strategy of fostering cultural quality, that is, knowledge where almost all officers appointed by the leadership have competency certifications that prove that these officers have indeed been tested. 6) Strategy to follow up, all services are carried out as well as possible and as optimally as possible even though improvements must always be reviewed and followed up. 7) Information system strategy, where SIM service officers have used an information system.